Effects of a Cooling Vest on Core and Skin Temperatures Following a Soccer-Specific Exercise Protocol - Carlos Lorente-González; Jose Vicente Beltran-Garrido; Abraham Batalla-Gavaldà; Francisco Corbi (Sports)
Background/Objectives: Cooling strategies are critical for optimizing athlete recovery and performance in team sports, yet practical, accessible solutions remain underexplored. This study evaluated the efficacy of a cool vest during a 15 min recovery period following 45 min of simulated soccer match play on core and skin temperature regulation. Methods: Forty-seven physically active males completed an exercise protocol replicating the physiological demands of a soccer half-match. Participants were randomized into an experimental group using a cool vest during recovery (IG, n = 24) or a control group (CG, n = 23) without cooling intervention. Results: Compared to CG, IG exhibited small but significant reductions in skin temperature (31.46 ± 0.67 °C vs. 32.40 ± 1.04 °C; ES = −0.24, 95% CI: −0.40 to −0.08; p = 0.003) and tympanic temperature (35.99 ± 0.45 °C vs. 36.54 ± 0.66 °C; ES = −0.43, 95% CI: −0.67 to −0.18; p < 0.001) 10 min post-exercise. These differences intensified to small and moderate effects at 15 min post-exercise for skin (31.07 ± 0.67 °C vs. 32.51 ± 0.91 °C; ES = −0.37, 95% CI: −0.53 to −0.21; p < 0.001) and tympanic temperatures (35.70 ± 0.42 °C vs. 36.65 ± 0.58 °C; ES = −0.71, 95% CI: −0.96 to −0.46; p < 0.001), respectively, with IG maintaining consistently lower values. No temperature changes were observed in CG. Conclusions: These findings demonstrate that a 15 min cool vest application during halftime effectively reduces core and skin temperatures, compared to passive recovery. This supports its utility as a practical, low-cost strategy for thermoregulatory management in soccer, warranting further investigation into its long-term performance benefits.